2018
DOI: 10.1088/2043-6254/aa9f4d
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biological activities of selenium and silver nanoparticles attached with bioactive phytoconstituents: green synthesized using Spermacoce hispida extract

Abstract: Selenium and silver nanoparticles (NPs) were synthesized using Spermacoce hispida aqueous leaf extract (Sh-ALE). The optimum condition required for the synthesis of Sh-SeNPs was found to be 30 mM selenious acid solution to Sh-ALE at the ratio of 4:46, pH 9, incubated at 40 °C for 10 min. On the other hand, for Sh-AgNPs the optimum condition was found to be 1 mM AgNO3 to the Sh-ALE solution at the ratio of 4:46, pH 8, incubated at 40 °C for 10 min. SEM analysis revealed that both the Sh-AgNPs and Sh-SeNPs are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 34 publications
2
18
0
4
Order By: Relevance
“…79 It was reported that the antioxidant potential of the plants-based SeNPs is may be due to the potential surface functional groups that cap and stabilize the nanoparticles and originate from the plant secondary metabolites. 32,62 The nutritionists and physicians routinely suggest using selenium supplemented food sources (nuts, mushrooms and cereals) to stay healthy. 13,71 The plants-based SeNPs are considered highly biocompatible in substituting the synthetic antioxidants as natural antioxidant embedding agents in food packaging material.…”
Section: Antioxidant Application Potential Of Plant-based Senpsmentioning
confidence: 99%
See 2 more Smart Citations
“…79 It was reported that the antioxidant potential of the plants-based SeNPs is may be due to the potential surface functional groups that cap and stabilize the nanoparticles and originate from the plant secondary metabolites. 32,62 The nutritionists and physicians routinely suggest using selenium supplemented food sources (nuts, mushrooms and cereals) to stay healthy. 13,71 The plants-based SeNPs are considered highly biocompatible in substituting the synthetic antioxidants as natural antioxidant embedding agents in food packaging material.…”
Section: Antioxidant Application Potential Of Plant-based Senpsmentioning
confidence: 99%
“…To overcome the serious side effects of drugs, nanobiotechnology can be a possible and effective solution to treat these deadliest diseases. 62 The plant-based SeNPs because of their non-toxic nature, excellent biocompatibility and unique bioactive properties can be one of the alternative strategies to control these devastating diseases. 5,17,41,72 In recent literature, the plant-based SeNPs have been explored to control the larva of mosquitoes.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanomaterials vary by size, distribution, and particle morphology (Service, 2000). Among nanometals, silver nanoparticles (AgNPs) are the most commonly used, given their range of biological activities and good chemical stability (Vennila et al, 2018, Prabhu and Poulose, 2012,). In the present work, we aimed to isolate and identify actinobacterial isolate from an insect Tapinoma simrothi.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the widely studied Au‐based NPs, Ag‐based NPs are seldom used in biomedical field, except for antimicrobial, mainly due to the serious cytotoxicity of Ag + released from Ag NPs . However, the unique properties of Ag NPs, such as special optical property, excellent electrical conductivity, good catalytic ability, bactericidal ability, and so on, are promising for biomedical application except their toxicity . Thus, efforts to reduce the biotoxicity of Ag are urgent needed.…”
Section: Introductionmentioning
confidence: 99%